Back Picture: Determination of Potential Scaffolds for Human Choline Kinase α1 by Chemical Deconvolution Studies (ChemBioChem 11/2013). Issue 11 (17th July 2013) - Sahún‐Roncero, María; Rubio‐Ruíz, Belén; Conejo‐García, Ana; Velázquez‐Campoy, Adrián; Entrena, Antonio; Hurtado‐Guerrero, Ramon
<x xml:space="preserve">Abstract</x> The back cover picture shows the the binding modes of a new CHOKa1 inhibitor. Using a chemical deconvolution approach based on the crystal structures of CHOKa1/1 and CHOKa1/2, A. Entrena, R. Hurtado‐Guerrero et al. have shown (p. 1291 ff.) that adenine and 1‐benzyl‐4‐(dimethylamino)pyridinium are the most efficient fragments in the molecules and that CHOKa1 is very flexible, adopting local conformational changes in the choline binding site.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>